(untitled) - Kubasakova, Iveta; Sulgan, Marian (Doprava a spoje, 2005)
Strategy system of logistic in business is conditional factor logistic fruitfulness. About prodigy ECR says in condition transformation landscape already several years. The new philosophy market ECR they would she had about successful switch-over young and old articles market fetch common improvement food-supply connection with goal-directed assortment behind superior costs for user.